The Influence Of Transactional Leadership And Work Motivation On Employee Performance Mediated By Job Satisfaction At Pt. Ratupanca Jaya Mandiri - Jihan Fahira; Suwandi, Suwandi (SEAN Institute, 2024)
The main focus of this study is to explore how transactional leadership and work motivation impact employee performance mediated by job satisfaction. Data were collected via Google Forms, with data analysis conducted using SmartPLS software. The findings of this study indicate a positive and significant impact; transactional leadership significantly affects employee performance. However, some variables, such as transactional leadership not affecting job satisfaction and work motivation not influencing employee performance, show that these relationships are not significant. Similarly, job satisfaction not significantly affecting employee performance and work motivation not significantly impacting job satisfaction indicate non-significant relationships at PT Ratupanca Jaya Mandiri. The mediation analysis reveals that job satisfaction plays a role in the correlation between transactional leadership and work motivation and impacts employee performance. This research is expected to help the company and improve employee performance.